Soil physical quality under different cotton cropping systems in the Cerrado of Bahia (Research, Society and Development, 2025)
Sandy soils of the Cerrado exhibit high structural fragility, especially when managed under conventional tillage and monocropping, which compromises their physical quality and the sustainability of cotton production. This study aimed to evaluate, after 10 years of cultivation, the effects of different cotton production systems, including conventional tillage and no-tillage systems with crop rotations, on the physical properties of a sandy-textured Red-Yellow Oxisol in the region of Luís Eduardo Magalhães, Bahia. The experiment was conducted in a randomized block design with six cropping systems and four replications. Undisturbed soil samples were collected down to 60 cm to assess the S index, bulk density, total porosity, macro and microporosity, water retention capacity, and available water. The results showed that differences among systems occurred mainly in the superficial layers (0–20 cm), which are more sensitive to management. The S index indicated that even treatments with cover crops maintained the soil in a degrading structural condition, with values